Integration 0f Village Library with Higher Education Library in Building Generation Reading Culture - Muhammad Eka Hidayatullah; Arif Munandar (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2019)
Various studies and the results of surveys conducted in Indonesia explain the least reading level, namely among children, especially in some areas, especially remote areas, so the need for a movement from the government to eradicate this. The construction of a center for science and information such as a village library is an effective step to foster the interest and reading culture of the generations. Over time, the central government has provided substantial funds to realize this in every village, leaving the village level government to continue in the form of quality development, such as building libraries and carrying out collaborative steps in the joint integration of university libraries as professional coaches. thus the transfer of knowledge will go well, which gives birth to professional village librarians and interest in reading generation increases then will slowly create my Source of better human beings born from the village.